MDCT Arthrography of the Shoulder - Fritz, Jan; Fishman, Elliot K.; Fayad, Laura M. (Seminars in Musculoskeletal Radiology, 2014)
High-resolution multidetector computed tomography (MDCT) arthrography of the shoulder can diagnose internal derangement of the glenohumeral joints including abnormalities of the rotator cuff, glenoid labrum, and articular cartilage. Isotropic data sets and postprocessing techniques enable interactive three-dimensional image analysis that is capable of reducing artifacts for metal implants. In this article, we review the indications for MDCT arthrography of the shoulder, highlight techniques and important features of the MDCT acquisition, and review normal and abnormal MDCT arthrography appearances of the glenohumeral joint.
Keywords: arthrography; glenohumeral joint; CT; shoulder